Intervention and peace. (2nd August 2018) - Levine, David K; Modica, Salvatore
Abstract: Intervention often does not lead to peace, but rather to prolonged conflict. Indeed, we document that it is an important source of prolonged conflicts. We introduce a theoretical model of the balance of power to explain why this should be the case and to analyse how peace can be achieved: either a hot peace between hostile neighbours or the peace of the strong dominating the weak. Non-intervention generally leads to peace after defeat of the weak. Hot peace can be achieved with sufficiently strong outside intervention. The latter is thus optimal if the goal of policy is to prevent the strong from dominating the weak.